Stephanocampta Mathot (Hymenoptera: Mymaridae): descriptions of two new species and the female of S. indica Anwar & Zeya from India and a key to world taxa - Palanivel, S.; Manickavasagam, S.; Triapitsyn, S. V. (Zootaxa, 2015)
Two new species of Stephanocampta Mathot (Hymenoptera: Mymaridae), S. andamanensis sp. nov. and S. huberi sp. nov., are described from Andaman Islands (Andaman and Nicobar Islands Union Territory) and Manipur, India. The previously unknown female of S. indica Anwar & Zeya is described. A revised key to the world species of Stephanocampta is provided. Stephanocampta serenellae Viggiani stat. rev. is transferred back to Camptoptera Förster, based on examination of the holotype male from Sri Lanka.